THE APPLICATION OF TIERS WORDS METHOD IN IMPROVING VOCABULARY MASTERY OF THE NINTH GRADE STUDENTS OF SMP SWASTA ANASTASIA - Meliala, Lorena Novica Bregina Br S; Sari, Anna Stasya Prima; Tarigan, Karisma Erikson (Kairos English Language Teaching Journal, 2022)
This research was primarily conducted to prove that the application of Tiers Words method could improve the vocabulary mastery of the ninth grade students of SMP Swasta Anastasia and to describe their responses towards the application of Tiers Words method in the processes of learning vocabulary. This is Classroom Action Research which was performed in two cycles. Each cycle consisted of three meetings. The quantitative data analysis showed that the students’ mean score increased continually from 29,44% in the pre-test, 62,27% in the formative test, and 78,30% in the post-test. The qualitative data analysis showed that the students gave good responses towards the application of Tiers Words method. They felt more enthusiastic and motivated to learn vocabulary after Tiers Words method was applied. To sum up, the application of Tiers Words method could improve the students’ vocabulary mastery. It is advisable that English teachers implement Tiers Words method in order to teach vocabulary.